1997
DOI: 10.1016/s0735-1097(97)00129-0
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Dependent Thrombin Generation in Patients With Hyperlipidemia

Abstract: Hypercholesterolemia, but not hypertriglyceridemia, was associated with increased platelet-dependent thrombin generation. Pravastatin normalized the generation of thrombin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 32 publications
2
50
1
1
Order By: Relevance
“…10,11 A body of evidence accumulating throughout the past decade, derived from a variety of in vitro and in vivo studies, indicates that statin therapy results in decreased thrombin formation. [5][6][7][8][9] Methodological approaches to the evaluation of the effect of HMG-CoA reductase inhibitors on thrombin formation encompass: (1) measurements of thrombin markers in venous blood drawn from treated subjects; (2) ex vivo perfusion systems that evaluate thrombotic potential of the blood obtained from these patients and exposed to thrombogenic substrate at various flow velocities; 27,29,30 (3) in vitro models of thrombin formation in recalcified plasma; 31 and (4) analysis of prothrombin activation, performed in consecutive blood samples collected from standardized bleeding-time wounds (the Simplate model). 32,33 Significant reductions in thrombin generation, reflected by lower levels of prothrombin fragment F1.2 (residues 1 to 156) cleaved from the prothrombin molecule by thrombin, were observed in hypercholesterolemic subjects.…”
Section: Thrombin Formation and Thrombin-mediated Coagulant Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 A body of evidence accumulating throughout the past decade, derived from a variety of in vitro and in vivo studies, indicates that statin therapy results in decreased thrombin formation. [5][6][7][8][9] Methodological approaches to the evaluation of the effect of HMG-CoA reductase inhibitors on thrombin formation encompass: (1) measurements of thrombin markers in venous blood drawn from treated subjects; (2) ex vivo perfusion systems that evaluate thrombotic potential of the blood obtained from these patients and exposed to thrombogenic substrate at various flow velocities; 27,29,30 (3) in vitro models of thrombin formation in recalcified plasma; 31 and (4) analysis of prothrombin activation, performed in consecutive blood samples collected from standardized bleeding-time wounds (the Simplate model). 32,33 Significant reductions in thrombin generation, reflected by lower levels of prothrombin fragment F1.2 (residues 1 to 156) cleaved from the prothrombin molecule by thrombin, were observed in hypercholesterolemic subjects.…”
Section: Thrombin Formation and Thrombin-mediated Coagulant Reactionsmentioning
confidence: 99%
“…29 Also in recalcified plasma, pravastatin 15 mg/d has been effective in reducing plateletdependent thrombin generation in hypercholesterolemic subjects. 31 Using a model of microvascular injury, which reflects TF-initiated blood coagulation, 32,33 we have demonstrated [37][38][39] that simvastatin 20 to 40 mg/d depresses thrombin generation in subjects with hypercholesterolemia. We found that at the site of hemostatic plug formation, depletion of prothrombin was reduced by 16%, whereas the rate of formation of prothrombin activation products, such as F1.2, prethrombin 2 (residues 274 to 579), and thrombin B-chain, was decreased by 27% and the time of their appearance was delayed by Ϸ60 seconds in hypercholesterolemic subjects receiving simvastatin.…”
Section: Thrombin Formation and Thrombin-mediated Coagulant Reactionsmentioning
confidence: 99%
“…Several studies have shown that statins reduce circulating levels of F1 ϩ 2 (15,16) and F1 ϩ 2 in samples from bleeding time wounds in patients with hypercholesterolemia (17,18). Aoki et al (19) showed that increased platelet-dependent thrombin generation in hypercholesterolemic patients normalizes after pravastatin treatment, whereas Szczeklik et al (17) found that simvastatin inhibits thrombin formation in bleeding time blood. Aspirin had no further effect on thrombin formation.…”
Section: -The Reduction Of Vwfag Was ϫ53% After Pravastatin Treatmenmentioning
confidence: 99%
“…One of the most important factors in these processes is thrombin generation (Wielders et al, 1997;Aoki et al, 1997). Our studies revealed increased thrombin generation during mastitis and metritis, especially in the first acute phase of the disease.…”
Section: Discussionmentioning
confidence: 60%
“…The more intense response in the metritis group in the first acute phase would be explained by the greater hypercoagulatory tendency in these animals. There is a lack of reports about thrombin generation in cows, although this parameter was previously used in humans for the estimation of prothrombotic state in atherosclerosis (Aoki et al, 1997). Moreover, increased thrombin generation may signal a thrombotic tendency in women using oral contraceptives, and in patients with coronary artery disease and deep vein thrombosis (Wielders et al, 1997).…”
Section: Discussionmentioning
confidence: 99%